Modern Food Habits and Its Impact on Human Health (International Journal of Innovative Research in Engineering & Management, 2023)
Modern food habits have undergone  significant changes due to urbanization, technological  advancements, and shifting lifestyles. These changes often  involve increased consumption of processed foods, high  sugar and fat intake, and reduced consumption of fresh fruits  and vegetables. Such habits have been linked to increased health issues like obesity, diabetes, cardiovascular diseases,  and other chronic conditions. Understanding and addressing  the impact of these modern food habits on health is crucial for promoting healthier lifestyles and preventing the  associated health risks.
Keywords: Modern Food Habits; Health Effects; Processed Foods; High Sugar Intake